Creating Inclusive Health Systems for People With Intellectual Disabilities: An International Study. Issue 4 (12th May 2020) - McConkey, Roy; Taggart, Laurence; DuBois, Lindsay; Shellard, Amy
Abstract: Background: Creating equitable access to mainstream health and healthcare service has been promoted as a means of addressing the health disparities experienced by people with intellectual disabilities (ID) globally. Specific Aims: This study addressed two questions: What strategic actions are most likely to bring about inclusive primary, secondary, and tertiary health systems for people ID? What are the system indicators that can be used to evidence a reduction in health disparities for this population? Method: A four‐phase study was undertaken involving an international expert advisory group, literature reviews, and individual interviews with 16 key informants from Special Olympics (SO). These led to an online international survey in which 61 respondents rated the relevance and feasibility of 30 strategic actions and system indicators to promote inclusive systems and reduce health disparities. Findings: All the strategic actions and system indicators were endorsed as relevant but less so for the feasibility of implementing them. Top‐rated strategic actions included the availability of policy statements and practice guidelines on making reasonable adjustments, mandatory training of health professionals on ID, and their involvement as cotrainers in staff training. Discussion: Implementing these strategic actions and system indicators will be a major undertaking and one that is unlikely to be speedily achieved given the many different policy and health systems that exist even within a locality as well as nationally and internationally. Nonetheless, the identified actions and indicators from this study can form the basis for improved access to health and for advancing the human rights of persons with ID.